Development and Refinement of a Targeted Sexual Risk Reduction Intervention for Women With a History of Childhood Sexual Abuse. Issue 4 (November 2017) - Senn, Theresa E.; Braksmajer, Amy; Hutchins, Heidi; Carey, Michael P.
Abstract: Childhood sexual abuse (CSA) is associated with sexual risk behavior in adulthood. Traditional sexual risk reduction interventions do not meet the unique needs of women who have been sexually abused. In the current paper, we describe the four-stage process we followed to develop and refine a targeted sexual risk reduction intervention for this population. First, initial quantitative work revealed that the intervention should address how maladaptive thoughts related to traumatic sexualization, trust, powerlessness, and guilt/shame (traumagenic dynamics constructs) influence current sexual behavior. Second, qualitative interviews with 10 women who reported a history of CSA ( M age = 34 years; 90% African American) as well as current sexual risk behavior provided support for targeting maladaptive thoughts associated with these traumagenic dynamics constructs. Third, based on the qualitative and quantitative results, we developed a 5-session, group-delivered intervention to address the maladaptive thoughts that occurred as a result of CSA, as well as the cognitive-behavioral determinants of sexual risk behavior. This intervention drew heavily on cognitive behavioral techniques to address cognitions associated with CSA and the links between these cognitions and current sexual risk behavior. Techniques from trauma-based therapies, as well as motivational techniques, were also incorporated into the intervention. Finally, we refined the intervention with 24 women ( M age = 33 years; 79% African American), and assessed feasibility and acceptability. These women reported high levels of satisfaction with the intervention. The resultant intervention is currently being evaluated in a small, randomized controlled trial. Highlights: Childhood sexual abuse (CSA) is associated with later sexual risk behavior. Typical sexual risk reduction interventions do not meet the needs of abused women. We developed a sexual risk reduction intervention addressing sexual trauma. Pilot testing indicated that the intervention was acceptable and feasible. The intervention is currently being evaluated with a small RCT.